PENGGUNAAN DINNER PLATE YANG ANTROPOMETRIS PADA AMERICAN SERVICE MENINGKATKAN KINERJA PELAYANAN MAHASISWA PRAKTEK DI RESTORAN SEKOLAH TINGGI PARIWISATA NUSA DUA BALI - Budiani, Ni Putu Ariesta; Adiputra, Nyoman; Surata, I Wayan (Jurnal Ergonomi Indonesia (The Indonesian Journal of Ergonomic); Vol 2 No 1 (2016): Volume 2 No 1 Juni 2016DO - 10.24843/JEI.2016.v02.i01.p05)
American-style service (American Service) priority to speed and accuracy amongwaitress while did the ministry. Therefore a waitress required to be able to carry a maximum of four plates at a time when doing service. The application of inappropriate tableware may associate with musculoskeletal complaints and fatigue, and affect the service performance in the restaurant. It is necessary for the application of ergonomic aspect especially appropriate equipment.This research was using an experimental study with the pre and post test control group design. This study involved fourth semester students, Restaurant Management Third Diploma of Nusa Dua Bali Tourism Institute as a subject as many as 36 people. The result showed significantly difference between control and treatment groups. In the treatment group  had  decreased  subjective  complaints  that include  musculoskeletal disorders about 38.7 % and general fatigue about 42.9 %. The length of presentation time decline 36.86%, while the quality of the presentation increased 65.01%. The decrease insubjective complaints occurred because the application of anthropometric dinner plate thatlighter 410 grams and has a shorter diameter 4.2 cm than previous plate. It is more convenient to carry even four at the time when presents to the guests. This is also showed an increase inservice performance. It can be concluded that the ergonomics  application  of using  appropriate anthropometric equipment in the American Service can improve the service performance among practice students in restaurant.
Keywords: Dinner plate, anthropometric, American Service, performance